Problems of Legal Regulation of Currency Circulation in Eastern Russia during the First World War - D. I. Petin (Сибирское юридическое обозрение, 2014)
The survey of the overall economic and financial situation in the Eastern Russia during the First World War is presented in the article. Special attention is paid by the author to the first experience of local emissions of money surrogates.